El femicidio en el Ecuador - Zambrano-Orvela, Marcela Anarcaly; Triviño-Vera, Karen Clemencia; Rivera-Segura, Gilma Nelly; Lemos-Espinoza, Aura Marina (IUSTITIA SOCIALIS, 2021)
El femicidio en el Ecuador